Analysis of Risk Factors and Gaps in Government Risk Allocation with Private Investor Risk Perceptions in the Toll Road Sector Using the PPP Scheme in Indonesia - Ayu Kartika Rachmawati; Zuliani Dalimunthe (Eduvest - Journal of Universal Studies, 2024)
Infrastructure development has an important role in a country's economic growth. Based on the 2020-2024 APBN plan, the total budget requirement for providing infrastructure is IDR. 2,058tn, where the government budget is 30% of the portion of budgeted funding needs. Due to the need for infrastructure development, the government initiated Government Cooperation with Business Entities (KPBU) in various infrastructure sector to accelerate infrastructure development in Indonesia, including toll road. This research was conducted to investigate identified risks along with risk mapping analysis to find out whether there is a gap in risk allocation between the government and private investors in implementing toll road PPPs in Indonesia. The method of this research is a qualitative study with data collection methods through interviews and questionnaires. From the research conducted, it is known that there are 7 (Seven) risk categories with 17 (Seventeen) risk events that are considered important by private investors. From the research conducted, it is known that there are 11 risk allocations that are appropriate and 6 allocations that are not in accordance with the risk perception of private investors in the toll road sector with the PPP scheme in Indonesia, namely the risk of differences in interest on land bailout loans, increases in construction costs, the risk of inflation rates and interest rates, the risk of rate adjustments being lower than projected, the risk of general regulatory (and tax) changes and the risk of political force majeure.